Identificación y estimación remota de floraciones de algas mediante la concentración de clorofila en el tramo inferior del río Uruguay y su incidencia sobre la actividad turística . - Zagel, Mauro Antonio (2019)
The Salto Grande reservoir and the final stretch of the Uruguay River are affected by eutrophication process that support the exponential development of algae; when it becomes visible to the naked eye we say that we are in the presence of algae flowering. During the development of this process the waters suffer an alteration of quality: when the concentration of algae exceeds the established limits, they are perceived as harmful due to their adverse effects on human health, economic activities such as tour ism and traditional fishing, and to the biological environment, affecting the development of fish, amphibians, shellfish, mammals and water birds. The use of data provided by remote sensing is beneficial, on the one hand, allowed to identify with an accept able level of detail, the algae blooms on the tourist beaches, places of interest where visitors carry out water activities; on the other hand, it allowed to recognize and estimate the concentration of algae (chlorophyll) in large areas, especially where the highest densities occur. The effectiveness of the method of image processing used was corroborated throughout the study area, where the identification and remote estimation of algal blooms was achieved through the concentration of chlorophyll; in the sa me way that proved to adapt to the different hydrological properties. The results obtained were satisfactory, allowing the differentiation of tourist beaches, chlorophyll (algae) and the water, even differentiating / identifying the algae where water acquires greater turbidity due to the presence of suspended particles. Therefore, this work is a contribution to the understanding of the HABs dynamics problem and to contribute to the interpretation of the different situations generated by HABs in the environment and to making decisions that contribute to the sustainable management of Uruguay river. For this purpose, a processing method is presented that generates digital images that are easy to understand, which allow a situation analysis and determine the affected areas, which will facilitate in situ prospecting to determine the type of algal flowering and assess its toxicity. In addition, digital images have the potential to be integrated into a geographic information system (GIS).